Access to finance and corporate emissions: A distributional perspective - Marcin Wolski (European Investment Bank (EIB), 2025)
We examine the relationship between capital structure and carbon intensity in manufacturing firms using a novel dataset that combines information from the EU Emission Trading System with firm-level financial accounts. Our findings indicate that higher financial leverage is associated with lower emission intensity at the firm level, primarily due to long-term debt, suggesting that improving access to such finance is generally conducive to corporate emissions reductions. However, this effect varies along the carbon intensity distribution. For firms with very high carbon intensity, increased leverage is linked to significant reductions in emissions, suggesting that better access to finance can facilitate the adoption of green technologies. Conversely, for firms that are already relatively carbon efficient, the effect disappears.
Keywords: C58; G32; Q51; Q56; Q58; 330; low-carbon transition; climate change; debt finance; financial leverage; EU ETS